The intimate world of men’s sexual problems: portuguese men’s and women’s narratives explicated through a mixed methods approach - Alarcão, V.; Roxo, L.; Virgolino, A.; Machado, F. L. (Sexuality and Culture, 2015)
This study used a mixed methods approach to investigate the intimate world of men’s sexual problems in Portugal, and particularly erectile dysfunction, focusing on the interplay between individual, societal and relational factors. First, a community-based survey was designed, with 323 primary health care users, to investigate how sociocultural factors influence experiences and representations of sexual problems. Second, a qualitative study, involving in-depth interviews with a subsample of ten heterosexual men, complemented by five heterosexual women’s narratives, concerning men’s sexual problems, was carried out to understand the meaning of sexual problems from a lay perspective. Statistical analysis of quantitative data was carried out through logistic regressions to evaluate the sociodemographic predictors of lay representations of sexual problems. Qualitative data were analyzed using an empirically grounded typology. The role of individuals in the construction of sexual dysfunctions, particularly erectile dysfunction, was explored using sexual script theory. Key findings revealed the impact of sexual problems on daily life. Gender analysis results contributed to the understanding of how men and women challenge the definition of sexual problems as normal changes versus dysfunctional changes. Specific patterns of change in sexual experiences and sexual problems were identified in the Portuguese gendered society, which can possibly be applied to other nations and cultures.